Visualization of Protein‐Specific Glycosylation inside Living Cells. Issue 6 (12th January 2016) - Doll, Franziska; Buntz, Annette; Späte, Anne‐Katrin; Schart, Verena F.; Timper, Alexander; Schrimpf, Waldemar; Hauck, Christof R.; Zumbusch, Andreas; Wittmann, Valentin
Abstract: Protein glycosylation is a ubiquitous post‐translational modification that is involved in the regulation of many aspects of protein function. In order to uncover the biological roles of this modification, imaging the glycosylation state of specific proteins within living cells would be of fundamental importance. To date, however, this has not been achieved. Herein, we demonstrate protein‐specific detection of the glycosylation of the intracellular proteins OGT, Foxo1, p53, and Akt1 in living cells. Our generally applicable approach relies on Diels–Alder chemistry to fluorescently label intracellular carbohydrates through metabolic engineering. The target proteins are tagged with enhanced green fluorescent protein (EGFP). Förster resonance energy transfer (FRET) between the EGFP and the glycan‐anchored fluorophore is detected with high contrast even in presence of a large excess of acceptor fluorophores by fluorescence lifetime imaging microscopy (FLIM). Abstract : Living proof : Protein‐specific glycosylation inside living cells was imaged by detecting FRET between an EGFP fused to the protein of interest and a fluorophore ligated to a metabolically incorporated N ‐acetylglucosamine derivative through an inverse‐electron‐demand Diels–Alder reaction. FRET can be detected with high contrast even in presence of a large excess of acceptor fluorophores by fluorescence lifetime imaging microscopy (FLIM).